Impact of an Interoception-Based Program on Emotion Regulation in Autistic Children - Kelly Mahler; Kerri Hample; Claudia Jones; Joseph Sensenig; Phoebe Thomasco; Claudia Hilton (Occupational Therapy International)
Purpose. The aim of this study was to determine the feasibility and effectiveness of a 25-week school-based intervention and its ability to improve interoception and emotion regulation in an autistic pediatric population. Method. One-group pre- and posttest design implementing The Interoception Curriculum: A Guide to Developing Mindful Self-Regulation in a self-contained school. Participants were 14 (11 male, 3 female) students between 9 and 19 years old. The Behavior Rating Inventory of Executive Function 2 (BRIEF-2) and the Caregiver Questionnaire for Interoceptive Awareness-2nd Edition (CQIA-2) were used to determine changes in interoceptive awareness and emotion regulation. Results. Statistically significant improvements were found between the preintervention and postintervention scores for both interoceptive awareness and emotion regulation. Conclusion. This was the first study to examine the Interoception Curriculum in its entirety, providing evidence that the use of the Interoception Curriculum is feasible in a school setting and suggests that this intervention is effective for improvement of interoception. Findings also suggest that this improvement in interoception is related to improvement in emotional regulation for an autistic pediatric population.